Actinide (An = Th–Pu) dimetallocenes: promising candidates for metal–metal multiple bonds. Issue 39 (16th September 2015) - Wang, Cong-Zhi; Gibson, John K.; Lan, Jian-Hui; Wu, Qun-Yan; Zhao, Yu-Liang; Li, Jun; Chai, Zhi-Fang; Shi, Wei-Qun
Abstract : Density Functional Theory (DFT) calculations on the actinide dimetallocenes An2 Cp*2 (Cp * = C5 (CH3 )5, An = Th–Pu) reveal the nature of actinide–actinide multiple bonding in these species. Abstract : Synthesis of complexes with direct actinide–actinide (An–An) bonding is an experimental 'holy grail' in actinide chemistry. In this work, a series of actinide dimetallocenes An2 Cp*2 (Cp * = C5 (CH3 )5, An = Th–Pu) with An–An multiple bonds have been systematically investigated using quantum chemical calculations. The coaxial Cp * –An–An–Cp * structures are found to be the most stable species for all the dimetallocenes. A Th–Th triple bond is predicted in the Th2 Cp*2 complex, and the calculated An–An bond orders decrease across the actinide series from Pa to Pu. The covalent character of the An–An bonds is analyzed by using natural bond orbitals (NBO), molecular orbitals (MO), the quantum theory of atoms in molecules (QTAIM), and electron density difference (EDD). While Th 6d orbitals dominate the Th–Th bonds in Th2 Cp*2, the An 6d-orbital characters decrease and 5f-orbital characters increase for complexes from Pa2 Cp*2 to Pu2 Cp*2. All these actinide dimetallocenes are stable in the gas phase relative to the AnCp * reference at room temperature. Based on the reactions of AnCp*2 and An, Th2 Cp*2, Pa2 Cp*2 and possibly also U2 Cp*2 should be accessible as isolated molecules under suitable synthetic conditions. Our results shed light on the molecular design of ligands for stabilizing actinide–actinide multiple bonds.